Clientelism, coalitions, and concessions: pragmatism in local elections and its democratic costs - Sadat, Anwar; Basir, Muh Askal (Frontiers in Political Science, 2025)
IntroductionThis study examines how clientelism, coalitions, and political concessions shape democratic costs in local elections, with political pragmatism as a mediating factor.MethodsWe conducted an anonymous survey of 100 voters in Southeast Sulawesi, Indonesia. Hypotheses were tested using PLS-SEM with bootstrapping to assess direct and indirect effects.ResultsClientelism does not directly affect democratic costs but has an indirect effect via political pragmatism. Coalitions reduce democratic costs. Concessions increase democratic costs both directly and indirectly. Pragmatism significantly predicts democratic costs. Measurement indices met conventional thresholds.Discussion/ConclusionPragmatism mediates how informal elite practices impact democracy: coalitions mitigate costs, while clientelism and concessions increase them. Policies should target transactional incentives and strengthen programmatic competition at the local level.